Exercise-Associated Hyponatremia: 2017 Update - Hew-Butler, Tamara; Loi, Valentina; Pani, Antonello; Rosner, Mitchell H. (Frontiers in Medicine, 2017)
Exercise associated hyponatremia (EAH) was initially described in the 1980s in endurance athletes and work done since then has conclusively identified that over-drinking beyond thirst as well as non-osmotic arginine vasopressin release are the most common etiologic factors. In recent years, EAH has been described in a broader variety of athletic events and also has been linked to the development of rhabdomyolysis. The potential role of volume and sodium depletion in a subset of athletes has also been described. This review focuses on the most recent literature in the field of EAH and summarizes key new findings in the epidemiology, pathophysiology, treatment and prevention of this condition.